KESEHATAN REPRODUKSI, HAK REPRODUKSI, DAN REALITAS SOSIAL - Biran Affandi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1997)
Reproduction process is really not a dangerous activity because it has gender rights reflected in the supporting components, i.e. ability, success, and safety. In the social reality, however, it is found different, as the high mortality rates of mothers and children, the appearance of sexual intercourse disease, and the side effects of contraceptive use. Biran Affandi, in his writing, describes social realities of the reproduction health which tends to be in the high risky point especially for women. All of these are as the consequence of the individuals who do not adhere their reproduction right.